Synthesis, properties, and catalysis of p-block complexes supported by bis(arylimino)acenaphthene ligands - Wang, Jingyi (2020)
Bis(arylimino)acenaphthene (Ar-BIAN) ligands have been recognized as robust scaffolds for metal complexes since the 1990 s and most of their coordination chemistry was developed with transition metals. Notably, there have been relatively few reports on complexes comprising main group elements, especially those capitalizing on the redox non-innocence of Ar-BIAN ligands supporting p-block elements. Here we present an overview of synthetic approaches to Ar-BIAN ligands and their p-block complexes using conventional solution-based methodologies and environmentally-benign mechanochemical routes. This is followed by a discussion on their catalytic properties, including comparisons to transition metal counterparts, as well as key structural and electronic properties of p-block Ar-BIAN complexes.